FILSHERIS: Inovasi E-Modul Bimbingan Digital Literacy Untuk Mencegah Hoax di Media Sosial. - Rahmayana, Sri; Aryani, Farida; Aswar, Aswar (Universitas Negeri Makassar, 2025)
This study aims to determine: 1) the need for an e-module for digitalliteracy guidance to prevent hoaxes on social media for high school students; 2) aprototype e-module for digital literacy guidance to prevent hoaxes on social mediafor high school students; 3) the validity test for the e-module for digital literacyguidance to prevent hoaxes on social media for high school students; 4) thepracticality test for the e-module for digital literacy guidance to prevent hoaxes onsocial media for high school students. This study used the Research andDevelopment (R&D) method with the ADDIE development model, which consists offive stages: Analysis, Design, Development, Implementation, and Evaluation. Afterconducting the validity test, the results were found to be valid based on expertassessments by subject matter experts and media experts. Furthermore,practicality testing by guidance counselors and small group trials showed excellentresults. Based on the analysis, it can be concluded that the Digital LiteracyGuidance E-Module to Prevent Hoaxes on Social Media is highly needed bystudents. It consists of four main topics, and has been proven valid and practicalfor use by students.